Ruang Perilaku Pantai Jagu Kota Lhokseumawe Melalui Lived Space - Mauliza, Nurul; Deni, Deni; A, Hendra (Jurnal Etnik: Ekonomi-Teknik, 2023)
Indonesia as an archipelago, has diverse cultures and tourism potential. Challenges such as conflicting regulations and lack of attention to the environment need to be addressed. Lhokseumawe City, particularly Jagu Beach, has tourism potential that is being developed as a Slum-free City Programme. Research is needed that is more in-depth about the area that occurs in the tourist space activities at Jagu Beach to understand and improve the quality of the Jagu Beach tourist space in order to become an area that supports living space. This research aims to understand the behaviour of tourists and local people in producing daily space and test the success of space production in tourist areas. The object of this research is the behavioural space of local people and tourists in Jagu Beach which is located on Jalan Iskandar Muda, Kampung Jawa Lama, District, Banda Sakti, Lhokseumawe City. This research uses mixed method. Based on research conducted using Henry Leuvebre's theory to see how the condition of the behavioural space of local tourists and local people in using the spaces contained in the Jagu Beach tourist area. The behavioural conditions carried out by visitors will affect the development of tourism, one of which is the facilities and infrastructure contained in the Jagu Beach tourism area. This is influenced by the needs of tourists in travelling. Based on physical research